2022
DOI: 10.1097/mnm.0000000000001551
|View full text |Cite
|
Sign up to set email alerts
|

Youtube videos for the most commonly applied radionuclide treatments: sufficient for patients as an information source?

Abstract: Objectives YouTube is one of the most popular online sources of information for patients. The purpose of the study is to analyze the quality of YouTube videos about the most commonly applied radionuclide treatments. Method Related radionuclide therapy videos were searched on YouTube in October 2021. The quality of the videos was assessed by using the Journal of the American Medical Association (JAMA) benchmark criteria, the DISCERN Scale and the Global Quality Scale (GQS). Results A total of 473 videos wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…For this purpose, content of medical videos may be evaluated with any of the parameters of JAMA, GQS and DISCERN. Studies have reported that there is a high positive correlation between these three parameters (18)(19)(20). In our study, significant positive correlations were found between JAMA score, GQS score, and DISCERN score.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…For this purpose, content of medical videos may be evaluated with any of the parameters of JAMA, GQS and DISCERN. Studies have reported that there is a high positive correlation between these three parameters (18)(19)(20). In our study, significant positive correlations were found between JAMA score, GQS score, and DISCERN score.…”
Section: Discussionsupporting
confidence: 70%
“…Similar to these studies, we found that 36 (48.0%) of the 75 videos included in our study were of high quality. However, there are also studies in the literature in which most of the videos are evaluated as low quality (12,17,19) and medium quality (20), which is inconsistent with these findings .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation